2008
DOI: 10.1044/0161-1461(2008/009)
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Early Intervention on Speech and Lexical Development for Toddlers With Cleft Palate: A Retrospective Look at Outcome

Abstract: The findings of this study indicated that early intervention as conducted by the speech-language pathologists in this study was not as effective as expected for this group of toddlers with cleft palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
2
25
0
4
Order By: Relevance
“…Infants and toddlers with CLP are frequently found to be at increased risk of impairment in speech and language development compared to their peers without CLP [17]. Studies have reported delays on global language development measures [18,19], as well as delays in vocabulary comprehension [5,6] and acquiring first words [20,21].…”
Section: Language Skills In Children With Clpmentioning
confidence: 99%
“…Infants and toddlers with CLP are frequently found to be at increased risk of impairment in speech and language development compared to their peers without CLP [17]. Studies have reported delays on global language development measures [18,19], as well as delays in vocabulary comprehension [5,6] and acquiring first words [20,21].…”
Section: Language Skills In Children With Clpmentioning
confidence: 99%
“…As mentioned earlier, possible language stimulation from parents could have explained the findings of significantly larger receptive vocabulary scores in toddlers with CL/P. We posit that this explanation may also hold with expressive vocabulary (Hardin-Jones and Chapman, 2008;Scherer and McGahey, 2004), bridging the expressive vocabulary score differences seen at the first time point, accounting for why the toddlers with CL/P did not show a significant difference in growth from the TD toddlers at the second time point.…”
Section: Expressive Vocabulary Growthmentioning
confidence: 85%
“…Such studies found early speech and language abilities to have implications for later language and literacy abilities in young children with CL/P (Broder et al, 1998;Scarborough, 2009;Snowling, 2000;Young et al, 2010), as reflected by uneven literacy skills and persisting receptive and expressive language difficulties (Broen et al, 1998;Jocelyn et al, 1996). Other research has suggested that early intervention in language skills can be effective if instituted (D'Antonio and Scherer, 2008;Hardin-Jones and Chapman, 2008;Kuehn and Moller, 2000;Pamplona and Ysunza, 2000;Pamplona et al, 2004;Scherer, 1999) under the age of five years -during the critical brain development period (Dowling, 2004). Given that clefting is perceived to place children with CL/P at a higher risk for language difficulties (Nagarajan et al, 2009), craniofacial teams are typically encouraged to provide extra intervention to help them catch up to their peers.…”
Section: Introductionmentioning
confidence: 97%
“…Hardin-Jones and Chapman[15] conducted a study to determine the effect of early intervention on speech and vocabulary development in 2.5-year-old children and found that children who received early speech therapy had a better performance than those who did not receive treatment or received it late.…”
Section: Discussionmentioning
confidence: 99%